Arceuthobium Species (Viscaceae) Parasitizing an Angiosperm: The Unique Case of A. azoricum in the Azores Islands - Elias, Rui B. (2024)
Arceuthobium azoricum Wiens & Hawksw. is a rare Azorean endemic epiphytic hemiparasite (mistletoe), which typically parasitizes branches of the gymnosperm Juniperus brevifolia (Hochst. ex Seub.) Antoine (Cupressaceae), which is also an Azorean endemic. Here, we describe a population of A. azoricum, on Pico Island, parasitizing Erica azorica Hochst. ex Seub. (Ericaceae), which is also an Azorean endemic. Our molecular analysis (using nuclear ribosomal internal transcribed spacer) showed no differences between individuals parasitizing Erica and Juniperus species. Moreover, a preliminary analysis showed no differences in morphological characteristics between accessions sampled from different hosts. Given that this is the first bona fide record of Arceuthobium sp. parasitizing an angiosperm, this population represents a unique host-shifting event, and its conservation is important because it may allow new insights into host recognition mechanisms in mistletoes. Immediate attention should be given to characterizing this Pico Island population using appropriate molecular methods and additional morphological analyses.